Sosialisasi Anti Perundungan (Bullying) Bagi Peserta Didik SDN 1 Batu Putih, Kecamatan Sekotong, Kabupaten Lombok Barat - Siti Yulianah M. Yusuf; Basuki Sri Hermanto; Nia Kurniati; Syaumudinsyah; Fitriah Kartini (CV. Multi Kreasi Media, 2024)
School is the second educational environment after the family. Schools play an important role in the psychological, social and emotional development of children as pupils. There's a lot of bullying nowadays done by kids around the school. The impact is concerned not only physical disturbance but also mental. Preventing negotiations is a shared responsibility for schools, parents, teachers, and society as a whole. Through dedication to the massacre, we endeavour to educate the younger generations in particular the children of the students in SDN 1 Batu Putih, Sekotong district, West Lombok district about negotiation / bullying. This activity is expected to benefit students in preventing bullying in the school surroundings.